Management of a patient undergoing sitting position craniotomy for acoustic neuroma with co-existing interstitial lung disease - Suvarna, Deepa; Baliarsing, Lipika; Gujjar, Pinakin; Agarwal, Rashmi (Journal of Neuroanaesthesiology and Critical Care, 2015)
A 38-year-old woman with acoustic neuroma associated with occupational interstitial lung disease (ILD) was successfully managed for sitting position craniotomy using carefully titrated desflurane-based anaesthesia. The anaesthetic challenges included maintenance an adequate depth of anaesthesia, reducing perioperative airway events and ensuring smooth recovery. While dealing with ILD patient in sitting position, careful risk assessment is important because it will help us predict the course of the perioperative events. Balanced general anaesthesia using desflurane fulfilled the requirement of good depth and smooth recovery in this patient. Though there are reports of maintenance of anaesthesia with other inhalational agents, there are scanty reports of using desflurane in these cases.
Keywords: Acoustic neuroma; desflurane; interstitial lung disease; sitting position craniotomy